Efektivitas Serum Anti Acne dari Limbah Kulit Durian (Durio Zibethinus Murr.) dengan Pengujian Berbagai Bakteri - Saputra, Sony Andika; Lailiyah, Munifatul; Mu'arofah, Binti (Indonesian Journal of Pharmaceutical Education, 2024)
Durian skin waste contains flavonoid compounds, triterpenoid tannins and alkaloids which have anti-bacterial activity that causes acne. This research aims to determine the characteristics of the anti-acne serum preparation formula from durian (Durio Zibethinus Murr) skin waste, the anti-bacterial activity and the stability of the preparation. The research method was preceded by making simplicia powder for the inner skin, which was then extracted using the maceration method with 96% ethanol solvent. The extract obtained was used as a preparation formula with concentrations of 5, 10 and 15%. The serum preparations obtained were evaluated for physical quality, tested for antibacterial activity and product stability during storage as well as freeze and thaw tests. The organoleptic results showed that the higher the concentration of the extract in the brown preparation, the homogeneity test showed that the serum was homogeneous. The pH test before and freeze and thaw test was found to be 5.45-5.87 and the pH was 5.20-5.74. The spreadability test before and after the freeze and thaw test was 8.15-8.88 cm and 7.78-8.4 cm. The anti-bacterial test showed that at a concentration of 15% in the serum preparation formulation the results were the same as the positive control with the MIC (MIC) value. Minimum Barrier) with P.acne, Staphylococcus aureus, Pseudomonas bacteria with barrier values of 18 mm, 18 and 15 mm. Based on the research results, it can be concluded that the durian skin extract serum preparation has good quality characteristics and has activity against acne-causing bacteria.